Course Transformation to Enhance Student Learning in Undergraduate Nursing Course: From a Self-Determination Theory Perspective. Issue 3 (May 2023) - Cho, Hyun Jin; Hannigan, Elaine; Davis, Jan E.; Levesque-Bristol, Chantal
Abstract: AIM: The purpose of the study was to investigate whether course transformation teaching strategies using repetitive quizzing and peer-tutor supplemental instruction help enhance students' learning experiences and learning outcomes based on self-determination theory. BACKGROUND: Undergraduate baccalaureate pharmacology and pathophysiology courses were redesigned as part of a campus-wide course transformation program to promote students' perceptions of learning and academic achievement. METHOD: Students in the nursing pathopharmacology course participated in the two-time online perception survey (pretest and posttest) and knowledge-based exams. RESULTS: Results revealed that the course transformation implemented to support students' basic psychological needs was significantly associated with both learning outcomes and students' feelings of competence while also decreasing attrition rates. CONCLUSION: Considering the depth and breadth of pathopharmacology content, the teaching intervention using repetitive quizzing and peer-tutor supplemental instruction may contribute to improving students' understanding of the course content while promoting their competence.